The ancient city : life in classical Athens & Rome - Connolly, Peter; Dodge, Hazel (New York : Oxford University Press, 1998)
Recreates the public buildings, temples, shops, and houses of ancient Athens and Rome, providing a window through which to look at the development of the cities and their architecture, and to discuss various aspects of daily life, including religion, food, drama, games, food, culture, and entertainment.
Includes bibliographical references (p. 253) and index.
Booklist.
School Library Journal starred.
Wilson's Senior High School.
Adult
Keywords: Athens (Greece) -- Civilization; Athens (Greece) -- Social life and customs; Rome -- Civilization; Rome -- Social life and customs; Athens (Greece) -- Civilization; Athens (Greece) -- Social life and customs; Rome -- Civilization; Rome -- Social life and customs